Ca2+ oscillations at fertilization in mammals. (1st October 2003) - Halet, G.; Marangos, P.; FitzHarris, G.; Carroll, J.
Abstract : The mouse egg provided the first direct measurement of Ca 2+ oscillations in any cell type. These sperm-induced Ca 2+ oscillations occur at a relatively low frequency, and can be detected up to 18–20 h after sperm–egg fusion. The Ca 2+ oscillations consist of two series of transients; the first lasts about 4 h, from metaphase II until interphase of the first cell cycle, and the second lasts the duration of the first mitotic division. This cell-cycle-regulated aspect to the pattern of Ca 2+ signalling at fertilization is reflected in the role of the Ca 2+ transients in stimulating exit from metaphase arrest. Recent developments have started to shed light on the mechanism initiating Ca 2+ oscillations at fertilization, on how the frequency of the oscillations is set, and on what determines their temporal pattern.